Confirmation of Aedes koreicus (Diptera: Culicidae) in Belgium and description of morphological differences between Korean and Belgian specimens validated by molecular identification - Versteirt, Veerle; Pecor, James E.; Fonseca, Dina M.; Coosemans, Marc; van Bortel, Wim (Zootaxa, 2012)
In 2008, specimens resembling Aedes (Finlaya) koreicus (Edwards) (also Ochlerotatus koreicus or Hulecoeteomyia kore-ica) were found in Belgium during a national mosquito survey (MODIRISK). Small but consistent differences were, how-ever, observed between the specimens described from Peninsula Korea and those found in Belgian. To achieve the correctidentification a detailed morphological comparison was made between the Belgian specimens and reference material fromKorean mainland and island populations housed at the Smithsonian Institution (Walter Reed Biosystematics Unit (WR-BU), Washington, USA). The identification was furthermore supported by molecular evidence based on the ND4 region(mtDNA) of available Korean and Belgian mosquito specimens. Morphological and molecular comparison confirmed theinitial identification of Aedes koreicus. Based on morphological characteristics, the species collected in Belgium mostlikely originated from Jeju-do, an island south of the Korean Peninsula. The observed dissimilarities between Korean andBelgian specimens resembled a number of morphological differences mentioned previously between female adults col-lected on the Korean Peninsula and Jeju-do. This is the first report of Aedes koreicus outside its natural distribution range.A correct and rapid identification of new invading and spreading vector species is crucial for the implementation of effec-tive control measurements. Hence a correct and easy accessible description of all possible variations of species arrivingin new areas is highly recommended. Therefore, a comparative morphological study on the Smithsonian material of thespecies from Korean mainland, island population and from Belgium is given, pictures of the main aberrant characteristicsand scanning electron microscope images of all stages of the species are included and molecular confirmation of the identification based on the mtDNA ND4 region is provided.